2018
DOI: 10.21833/ijaas.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of social networking sites on study habits among Saudi nursing students in Hail University

Abstract: The research investigates pedagogical influences of social networking web sites (SNS) of nursing training in Saudi Arabia committed to study the habits of nursing student in the computerized age. Consequently, this investigation was directed fundamentally to decide the connection between use of SNS as indicated by sort, recurrence, hours every week and impact of others, and study behaviour with respect to time administration, fixation and inspiration. A correlational research configuration was utilized as a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The negative and positive aspects of SNS utilization are a contentious issue that has yet to be resolved because SNSs can be addictive and their improper usage may lead to less positive outcomes. Studying is a skill, and developing study habits is vital for the academic performance of students [33]. Some studies strongly advocate the use of SNSs as a means of becoming academically successful.…”
Section: Discussionmentioning
confidence: 99%
“…The negative and positive aspects of SNS utilization are a contentious issue that has yet to be resolved because SNSs can be addictive and their improper usage may lead to less positive outcomes. Studying is a skill, and developing study habits is vital for the academic performance of students [33]. Some studies strongly advocate the use of SNSs as a means of becoming academically successful.…”
Section: Discussionmentioning
confidence: 99%
“…The students engaged with a variety of social media, with the most commonly used medium being Facebook, followed by Twitter and WhatsApp. Those studies that reported frequency of social media use found that students used social media on a daily basis (AlSaqri et al., 2016; Al‐Shdayfat, 2018; Duke et al., 2017; Ferguson et al., 2016; Mather et al., 2016; Sadd, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Through social media, students could chat, get updates, upload photos and share information (Al‐Shdayfat, 2018; Duke et al., 2017; Mather et al., 2016; Nyangeni et al., 2015; Pimmer et al., 2018; Quansah et al., 2016; Sadd, 2019). In addition, some types of social media such as Twitter and Skype allowed the students to explore the world by connecting them with people from different countries and cultures (AlSaqri et al., 2016; Ferguson et al., 2016). In summary, social media facilitated students' daily communication, decreased their feelings of boredom and strengthened their friendship ties (Warshawski et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying is a skill, and developing study habits is vital to the progress of the academic performance of students [33] . There is available literature that highly contends the use of SNS as means to become academically successful, such as in a study that mentioned that Facebook and SNS were considered the biggest distraction among college students, subsequently affecting their study habits and grades [34] .…”
Section: Discussionmentioning
confidence: 99%